A caffeic acid electrochemical sensor amplified with GNR/CoFe2O4@NiO and 1-Ethyl-3-methylimidazolium acetate; a new perspective for food analysis. (September 2022) - Mostafazadeh, Reza; Ghaffarinejad, Ali; Tajabadi, Fariba
Abstract: Determining Caffeic acid is important as an antioxidant compound in food. In this study, caffeic acid (CA) was measured using a carbon paste electrode modified with GNR/CoFe2 O4 @NiO and 1-Ethyl-3-methylimidazolium acetate (EMIM Ac) as ion liquid. A simple sensor showed a higher current than a bare carbon paste; thus, it can be said that the modified electrode has a higher sensitivity for detecting CA. The linear range of this sensor and its detection limit was equal to 0.01–100.0 μM and 0.01 μM, respectively. Moreover, the developed electrode indicated outstanding selectivity in the presence of several interferences, high sensitivity, reproducibility, and long-term stability. The percentage recovery of CA obtained with the developed sensor affirmed its reliability for CA determination in real samples. The modified sensor's accuracy was confirmed to identify this analyte according to the results. Highlights: Determining Caffeic acid is important as an antioxidant compound in food. Carbon paste electrode was modified by GNR/CoFe2 O4 @NiO as a Caffeic acid sensor. The fabricated sensor was evaluated by voltammetry methods. A wide linear range was obtained between 10 nm and 100 μM. Caffeic acid was measured in drinking water, cherry juice, and coffee beverages.